Respon Pertumbuhan Bayam Brazil (Alternanthera sissoo) terhadap Pemberian POC Lindi dan Bokashi Kotoran Kambing - Ary Astuti; Pramono Hadi; Libria Widiastuti (MAN 4 Kota Pekanbaru, 2026)
This study evaluated the effects of leachate-based liquid organic fertilizer (LOF) and goat manure bokashi on the growth and yield of Brazilian spinach (Alternanthera sissoo). A factorial completely randomized design was applied with three levels of leachate (0, 250, and 500 ppm) and three levels of bokashi (0, 120, and 240 g per polybag). Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test at 5%. Leachate application did not significantly affect plant height, root length, root volume, leaf number, or fresh biomass. In contrast, bokashi significantly increased leaf number and fresh biomass, while no significant interaction between treatments was observed. These results indicate that goat manure bokashi improves vegetative growth and yield of Brazilian spinach, whereas the tested leachate concentrations were insufficient to enhance plant performance. Further studies are recommended to optimize leachate dosage and combination with inorganic fertilizers.